ANALYSIS CHANGES AND MANAGEMENT STRATEGY OF MANGROVE FOREST IN GUNUNG PALUNG NATIONAL PARK, NORTH KAYONG REGENCY, WEST KALIMANTAN - Nurul Ihsan Fawzi (COJ (Coastal and Ocean Journal), 2017)
The inventory of global mangrove forest loss reached 12% from 1975 – 2005. The aim of this research is to find the change of mangrove forest in Gunung Palung National Park and its surrounding and to evaluate mangrove forest management. The method for mangrove forest mapping, we used Landsat TM image acquired on 12 September 1989 and 3 October 1989, Landsat ETM + images acquired on 25 June 2002, 11 July 2002 and 28 August 2002, and Landsat 8 (OLI) image acquired on 19 March 2016 and September 27, 2016. Analyzing mangrove forest change using subtraction methods and SWOT analysis for appropriate management evaluation. The result, we found the distribution and extent of mangrove forest with mapping accuracy for 2016 is 95%. Mangrove forests in the Gunung Palung National Park area have been decreased, i.e. the respective areas in 1989, 2002, and 2016 were 355.43 ha, 355.42 ha, and 204.63 ha. In 1989 and 2002 mangrove forests were unchanged, and by 2016 there was deforestation of 150.79 ha. For a comprehensive analysis, we using buffer along 10 km from National Park border, we found the change of mangrove forest area in 1989, 2002 and 2016 was 3,106.85 ha, 2,895.99 ha, and 2,260.98 ha, respectively; or there has been deforestation of 845.87 ha. The main caused of deforestation is the conversion of mangrove forest to agricultural by communities due to tenure conflict with National Park. Conflict resolution strategies and management are Conflict resolution strategies and their management are joint forest management with respect to an agreement for conservation, mangrove forest inventory, and protection of remaining mangrove. Keywords angrove forest change, coastal management, Landsat image, Gunung Palung National Park